Oncologic outcomes following neoadjuvant immunochemotherapy in locally advanced oral squamous cell carcinoma - Li, Gang; Wang, Jiheng; Fang, Qigen; Dai, Liyuan; Du, Wei (Frontiers in Immunology, 2025)
BackgroundTo assess the oncologic outcomes in patients with oral squamous cell carcinoma (SCC) who underwent treatment with radiotherapy (RT) or chemoradiation therapy (CRT) following neoadjuvant immunochemotherapy and surgery.MethodsData from patients who underwent neoadjuvant immunochemotherapy, surgery, and adjuvant therapy were collected prospectively and analyzed retrospectively. The primary outcomes assessed were 3-year overall survival and locoregional control. Secondary endpoints included the objective response rate (ORR), rates of pathologic complete response (pCR) and major pathologic response (MPR), as well as safety.ResultsA total of 137 patients were included in the analysis. Neoadjuvant therapy yielded an ORR of 81.7%, with pCR and MPR achieved in 47 and 73 patients, respectively. Grade III and IV adverse events were rare, comprising only 1.6% of all events. The addition of adjuvant chemotherapy to RT did not show a significant reduction in the risk of locoregional recurrence. However, with regards to overall survival, the hazard ratios were 0.85 (95% CI: 0.73-0.96) for the MPR group and 0.66 (95% CI: 0.37-0.89) for the pCR group, both significantly higher than that in patients with incomplete pathologic response. The addition of adjuvant chemotherapy to RT was associated with a 5% reduction in the risk of mortality (95% CI: 1%-14%), the protective effect of CRT was the most obvious in patients with MPR.ConclusionNeoadjuvant immunochemotherapy demonstrated high safety and efficacy in oral SCC. CRT was superior to RT in terms of overall survival especially in patients with MPR when administered following neoadjuvant immunochemotherapy and surgery.